Estimating permeability functions of Singapore residual soils - Agus, Setianto Samingan (2011)
About two thirds of Singapore's land area is covered with residual soils with various depths of weathering. For geotechnical analyses, information pertaining to the hydraulic properties (coefficient of permeability and water retention capability) of these soils is important. Residual soils above the groundwater table commonly exist under unsaturated conditions and the characterisation of residual soils includes both saturated and unsaturated soil properties (e.g., permeability). As determination of the unsaturated coefficient of permeability is tedious, time consuming and labour intensive, predictive methods are often preferred. This paper describes the estimation of permeability functions (i.e., saturated and unsaturated coefficients of permeability) of Singapore residual soils using the soil–water characteristic curve and saturated coefficient of permeability obtained in the laboratory for a number of Singapore residual soils. It has been found that the predictive methods give good agreement with the experimental data and thus provide good estimate of the permeability function.